Neuroscience-Based Fiqh Learning to Strengthen Spirituality and Religious Cognition of Students in Madrasah: Pembelajaran Fiqih Berbasis Neurosains Untuk Penguatan Spiritualitas Dan Kognisi Religius Peserta Didik Di Madrasah - Milda Muliati Muliati; Atmunadi Atmunadi; Aulia Zahara (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This research is based on the phenomenon of declining interest and understanding of Fiqh material by students, which has been taught solely textually and cognitively, without considering the neuroscience aspects related to how the brain works in understanding and internalizing spiritual values. This background encourages the need for innovation in neuroscience-based Fiqh learning as an approach that integrates the biological, psychological, and spiritual potential of students. The purpose of this study is to analyze the application of neuroscience-based Fiqh learning in strengthening the spirituality and religious cognition of students in Islamic schools. This study uses a qualitative approach with descriptive methods through observation, interviews, and documentation studies of teachers and students at Islamic junior high schools. Data were analyzed using interactive reduction, presentation, and conclusion drawing techniques. The results show that the application of neuroscience-based Fiqh learning can increase emotional engagement, awareness of worship, and reflective abilities of students in understanding the laws of Fiqh. In addition, this approach fosters a balance between cognitive and affective aspects so that Fiqh learning is not only informative, but also transformative. Thus, the integration of neuroscience into Islamic jurisprudence (Fiqh) learning is an effective strategy for developing a generation of madrasah students who are faithful, intelligent, and have religious character.